CORELATION OF FAMILY ECONOMIC STATUS WITH STUNTING IN THE WORKING AREA OF PUSKESMAS SAMBAU, KOTA BATAM - Siti Iqbalwanty; Meirina Daulay (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2021)
Stunting is a chronic nutritional problem that arises as a result of prolonged malnutrition. The incidence of stunting arises as a result of long-standing conditions such as poverty, improper parenting behavior, and frequent illnesses due to poor hygiene and sanitation. According to WHO, the prevalence of stunting in Indonesia is around 8.9 million, in Riau Islands as many as 262 cases, in Batam City as many as 154 cases. The purpose of this study was to determine the relationship between economic status and the incidence of stunting. Method : The research method used was an analytic survey with a cross sectional approach. Conducted at Posyandu in the working area of Puskesmas Sambau, Batam City, the study was conducted for 6 months, the population in this study were all mothers who had toddlers aged 24-59 months, with a sample of 58 respondents, using purposive sampling technique. Data collection using a questionnaire. Data presented in tabular and textual form, data analysis using Chi-square. Result : The results obtained were low economic status (55.6%), and the incidence of stunting (39.7%). The results of the statistical test of economic status obtained a p-value of 0.004, so Ho is rejected. Conclusion :. There is a relationship between Parents' Knowledge of Toddler Nutrition and Family Economic Status with the Incidence of Stunting in Toddlers at the Posyandu in the working area of Puskesmas Sambau, Batam City. It is hoped that parents will pay more attention to the nutrition of children under five so that the incidence of stunting can be reduced.